2015
DOI: 10.1007/s11356-015-4454-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals and metalloids in tissues of two frog species: Rana tigrina and Euphlyctis cyanophlyctis from industrial city Sialkot, Pakistan

Abstract: In the present study, we investigated the concentrations of Ni, Fe, Pb, Cu, Co, Zn, Cd, Mn, and Cr in selected body tissues (liver, stomach, kidney, heart, lungs, and skeletal muscles) of two frog species: Rana tigrina and Euphlyctis cyanophlyctis captured from industrial wastewater of Sialkot city known worldwide for its tanning industry. The both frog species had darker appearance, distinctively different wet body weight, and snout-vent length. The results revealed that the heavy metal concentrations were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…All the heavy metals studied accumulated more in the lung and liver. This agreed with the finding of Bawuro (2018) who recorded more heavy metals in the lung of fish and Qureshi et al, (2015) who recorded more metals in the liver of frogs. Lung accumulated more heavy metals likely because of its prominent function in gaseous exchange (Singh et al, 2011).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…All the heavy metals studied accumulated more in the lung and liver. This agreed with the finding of Bawuro (2018) who recorded more heavy metals in the lung of fish and Qureshi et al, (2015) who recorded more metals in the liver of frogs. Lung accumulated more heavy metals likely because of its prominent function in gaseous exchange (Singh et al, 2011).…”
Section: Resultssupporting
confidence: 91%
“…High accumulation of Zn in all the organs/parts of frogs may be due to the specific adaptive mechanism of the frogs to absorb Zn from the habitat for onward transfer to kidney for metabolism. It may also be from agro-chemicals (fungicides) used in the farms as reported by Qureshi et al, (2015). This is in line with the finding of Taiwo et al, (2014) who recorded high concentration of Zn in tissue of H. occipitalis.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Table 1 shows the THQ values derived using trace element concentrations, reference dosage, and daily average frog leg eating. THQ levels detected were below the limit value of 1, indicating that trace elements from P. Mani et al, 2021Zhelev et al, 2020Tyokumbur and Okorie, 2011Qureshi et al, 2015 ridibundus' leg may not have harmful health impacts on humans when consumed regularly. These risk calculations were made entirely according to the raw material results.…”
Section: Risk Estimationsmentioning
confidence: 90%
“…Similar results were obtained from other studies. In a study that was carried out by Qureshi et al (2015), high levels of Cu and Cd concentrations were detected in the liver and kidney of Rana tigrina and Euphlyctis cyanophlyctis frogs inhabiting in a water source polluted industrial wastes in Sialkot District (Pakistan). In another study, Fe, Mn, Pb, Zn, Cu, Cr, and Cd metals were detected in the livers, skin, and digestive systems of Rana esculenta living in the Guma River Wetland (in Nigeria), and it was reported that Cd, Cu, and Zn exceeded the limits set by the WHO (Shaapera et al, 2013).…”
Section: Discussionmentioning
confidence: 99%